Women leadership in higher education: exploring enablers and challenges from middle-level academics’ perspective - Lei Mee Thien; Hooi Lian Lim; Ahmad Firdaus Ahmad Shabudin; Rahimi Che Aman; Aziah Ismail; Wan Fatma Zuharah; Muhammad Muftahu (Humanities & Social Sciences Communications)
Abstract The scarcity of literature in higher education addressing the enablers or challenging factors influencing the progression of women academics from middle-level to senior leadership roles is noteworthy. This study aims to explore the factors that enable or impede the advancement of middle-level women academics and identify recommendations for promoting women leadership in higher education institutions. This qualitative study has collected interview data from 17 informants from five Malaysian public universities. The thematic analysis revealed four enablers and three challenges faced by women in academic leadership. The thematic analysis revealed four enabler factors - gender-neutral policies, management of multiple roles, core personal competencies, and the presence of mentors and role models. Conversely, traditional women’s roles, social stigma, and personal factors were identified as factors that hinder women’s leadership in universities. The findings underscore the importance of implementing gender-neutral policies to foster inclusivity, the establishment of formal mentorship programmes, and cultivating multitasking skills among women. Understanding the dynamics from the perspective of middle-level women academics is essential for crafting a more equitable and supportive institutional environment to equip them with the necessary resources and support to transition into senior leadership positions smoothly, ultimately strengthening the leadership pipeline within the institution.